Estimation of nonclassical properties of multiphoton coherent states from optical tomograms. Issue 12 (12th July 2018) - Laha, Pradip; Lakshmibala, S.; Balakrishnan, V.
Abstract: We have examined both single and entangled two-mode multiphoton coherent states and shown how the 'Janus-faced' properties between two partner states are mirrored in appropriate tomograms. Entropic squeezing, quadrature squeezing and higher-order squeezing properties for a wide range of nonclassical states are estimated directly from tomograms. We have demonstrated how squeezing properties of two-mode entangled states produced at the output port of a quantum beamsplitter are sensitive to the relative phase between the reflected and transmitted fields. This feature allows for the possibility of tuning the relative phase to enhance squeezing properties of the state. Finally, we have examined the manner in which decoherence affects squeezing and the changes in the optical tomogram of the state due to interaction with the environment.